PAOLO: A Polarimeter Add‐On for the LRS Optics at a Nasmyth focus of the TNG1. Issue 2 (February 2014) - Covino, S.; Molinari, E.; Bruno, P.; Cecconi, M.; Conconi, P.; D'Avanzo, P.; di Fabrizio, L.; Fugazza, D.; Giarrusso, M.; Giro, E.; Leone, F.; Lorenzi, V.; et al.
Abstract We describe a new polarimetric facility available at the Istituto Nazionale di AstroFisica / Telescopio Nazionale Galileo at La Palma, Canary islands. This facility, PAOLO (Polarimetric Add‐On for the LRS Optics), is located at a Nasmyth focus of an alt‐az telescope and requires a specific modeling in order to remove the time‐ and pointing position‐dependent instrumental polarization. We also describe the opto‐mechanical structure of the instrument and its calibration and present early examples of applications. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)